Neuroclusal rehabilitation and planas direct tracks in the posterior crossbite treatment - Garbin, Artênio José Isper; Wakayama, Bruno; Rovida, Tânia Adas Saliba; Garbin, Cléa Adas Saliba (Faculdade São Leopoldo Mandic, 2017)
ABSTRACTObjective: To evaluate the effectiveness of neuroclusal rehabilitation treatment using Planas Direct for posterior crossbite correction.Methods: This is a clinical study in which 43 children were selected, of both sexes, between 3 and 6 years old, diagnosed with posterior crossbite and midline deviation. Interviews were conducted with the parents in order to ascertain the practice of harmful habits. The treatment was based on neuroclusal rehabilitation in order to investigate and eliminate the occlusal obstacles which depreciate the stomatognathic system. The aim of the study was also to reprogram the affected neuromuscular activity. Planas direct were performed on crossed teeth in order to restructure the neuroclusal area and the stomatognathic system, as well. Epi Info software, 3.5.4 for Windows, through the distribution of frequencies and the Pearson chi-square test were used for statistical analysis.Results: Occlusal restoration in 79% of children was performed however 21% abandoned treatment. The crossbite and midline correction period ranged from from 14° to the 91° treatment. Significant associations of the variables were observed as follows: deleterious habits (p = 0.0001) and midline deviation (p = 0.0001) at the beginning or end of treatment.Conclusion: It was concluded that the neuroclusal rehabilitation and Direct Slopes Planas were effective in correcting the posterior crossbite.

RESUMOObjetivo: Avaliar a eficácia do tratamento da reabilitação neuroclusal com as Pistas Diretas Planas na correção das mordidas cruzadas posteriores.Métodos: Trata-se de um estudo clínico no qual foram selecionadas 43 crianças, de ambos os sexos, entre 3 e 6 anos de idade, diagnosticadas com mordida cruzada posterior funcional e desvio de linha média. Foram realizadas entrevistas com os responsáveis dos participantes, para averiguar a prática de hábitos deletérios. O tratamento baseou-se na reabilitação neuroclusal, no intuito de investigar e eliminar os empecilhos oclusais que depreciam o sistema estomatognático, e assim, reprogramar a atividade neuromuscular afetada. Foram confeccionadas as Pistas Diretas de Planas nos dentes cruzados, a fim de reestrutura os estímulos neuroclusais e o sistema estomatognático. Na análise estatística, utilizou-se o software Epi Info software, versão 3.5.4 for Windows, por meio da distribuição das frequências e o Teste do Qui-quadrado de Pearson.Resultados: Houve o restabelecimento oclusal em 79% das crianças, visto que 21% abandonaram o tratamento. O período de correção da mordida cruzada e linha média compreenderam-se ao 14° ao 91° de tratamento. Foram observadas associações significativas das variáveis: hábitos deletérios (p=0.0001) e desvio de linha média (p=0.0001) no início e final do tratamento.Conclusão: Conclui-se que a reabilitação neuroclusal e as Pistas Direta de Planas foram eficazes na correção das mordidas cruzadas posteriores.
Reabilitação neuroclusal e pistas diretas de planas na correção da mordida cruzada posterior
Keywords: Malocclusion; Occlusal adjustment; Orthodontics.; Má oclusão; Ajuste oclusal; Ortodontia.